IMPLEMENTASI MANAJEMEN TENAGA PENDIDIK DI MTs MUHAMMADIYAH SUKARAME BANDAR LAMPUNG - Oki Dermawan (Universitas Islam Negeri (UIN) Sumatera Utara, 2024)
Abstract: Madrasa is obliged to have a good management system in order to get an educator who has excellent and a certain quality human resources. This study aims to determine the implementation of the management of educators at MTs Muhammadiyah Sukarame Bandar Lampung which focuses on recruitment process, selection, coaching, compensation, and educators evaluation at Mts. Muhammadiyah Sukarame Bandar Lampung. This research is a naturalistic qualitative. The research data are taken from two sources of data, namely secondary data and primary data, using the following data collection methods: interviews, observations, and documentation. The data analysis technique is in the form of qualitative analysis, including data reduction, data presentation, and verification or drawing conclusions. The results of this study indicate that the implementation of the recruitment of educators begins with reviewing the needs of educators, forming committees, implementing recruitment, and monitoring. The implementation of the educators selection begins with preparing an effective selection program, forming a committee and selection model, implementing selection, and monitoring. The process of developing educators includes developing educators through monthly meetings coordinated by school principal and school supervisors, developing students including curriculum development and several activities that improve the skills and abilities of educators, and supervising the implementation of student development. Compensation for educators is given in the form of salaries or wages and incentive compensation as a reward for educators who work well. The educators evaluation includes systematic learning planning, evaluation of educators coordinated by school principal, and supervision of evaluation activities.